Hubungan Kekuatan Otot Tungkai Dan Lari Sprint 60 Meter Dengan Kemampuan Lompat Jauh Gaya Jongkok Pada Siswa Putra SMPN 7 Pujut Tahun Pelajaran 2017/2018 - Robby Cahyadi; Lalu Sapta Wijaya K; Adi Suriatno (Universitas Pendidikan Mandalika, 2018)
The long jump is a form of jumping motion lifting the foot upwards in an effort to carry weight as much as possible in the air (flying in the air) which is performed quickly and by doing repulsion on one leg to reach the distance as far as possible. Based on the results of the observations, each student sometimes performed a good jump but performed poor jump as well. According to researcher, the average student has unstable limb muscle strength and speed. This motivated the researcher to find the contribution of the limb muscle strength and 60 meters sprint toward the long jump ability of squats style on the male students of SMPN 7 Pujut in 2017/2018 academic year. This study aims to determine the correlation between the limb muscle strength and 60 meters sprint toward the long jump ability of squats style on the male students of SMPN 7 Pujut in 2017/2018 academic year. This research is a correlation research. The instruments used in the study were the limb muscle strength test, 60 meter sprint test and long jump of squat style ability. The subjects of this study were the students of SMPN 7 Pujut which amounted to 20 students. The data analysis technique used the test analysis of multiple linearity correlation, simple correlation coefficient test by product moment correlation formula, and multiple correlation. The results of this study show that the correlation of limb muscle strength (X1) toward the long jump ability (Y) is 0.490., the 60 meters sprint (X2) toward the long jump ability (Y) is 0.447, and the correlation between limb muscle strength (X1) and 60 meters sprint (X2), toward the squat style long jump ability (Y) is 0.792. It can be concluded that there is correlation between the limb muscle strength and 60 meters sprint toward the long jump ability of squats style on the male students of SMPN 7 Pujut in 2017/2018 academic year.